Detection of Streptococcal Pyrogenic Exotoxin Genes SpeA and SpeB in Isolated Streptococcus pyogenes from Children with Pharyngitis, Gezira State, Sudan - Balla, Minas Mohamed; Mergani, Adil; Medani, Mohamed Elamin A. M. E.; Abakar, Adam Dawoud; Dafalla, Ameer Mohamed (Research Perspectives of Microbiology and Biotechnology Vol. 2, 2024)
Background: Streptococcus pyogenes (group A streptococcus, GAS) is an important human bacterial pathogen. This organism possesses many virulence factors, Streptococcal pyrogenic exotoxin one of these and the presence of virulence factors is often related to the severity of the disease. Aim: The present study aimed to detect Streptococcal pyrogenic exotoxin (Spe) A and Spe B in isolated Streptococcus pyogenes. Methods: Two hundred throat swab samples were collected in across sectional study from children with pharyngitis referred to Pediatric Teaching hospital and ENT hospital Wad medani, Sudan, from January to November 2021. Questionnaire was filled to collect clinical and demographic data. In order to isolate Streptococcus pyogenes, throat swabs were obtained and processed according to normal microbiological protocol. Using the Kirby Bauer disk diffusion method, antimicrobial susceptibility testing was performed on all GAS isolates in accordance with clinical laboratory standard institute (CLSI) criteria. Multiplex PCR was used to identify the Spy 1258 gene as well as the streptococcal pyrogenic exotoxins SpeA and SpeB. Results: Amongst the Two hundred collected samples fifty-one isolates, (25.5%) were identified as S. pyogenes. Antibiotic susceptibility testing showed that all the GAS isolates were sensitive to Azithromycin and Penicillin. Sensitivity to Erythromycin, Gentamicin, Clarithromycin, Amoxicillin and Cephalexin were 88.2%, 86.3%, 45.1%, 41.2%, 13.7%, respectively. SpeA was detected in 17(33.3%) and SpeB in 48(94.1%). Conclusion: The rate of Streptococcus pyogenes was 25.5% in children diagnosed with pharyngitis. Streptococcal pyrogenic exotoxin genes SpeA and SpeB were detected in 17(33.3%) and 48(94.1%) respectively of Streptococcus pyogenes Sensitivity of Streptococcus pyogenes to Penicillin and Azithromycin was 100%, penicillin is the drug of choice for the treatment of GAS pharyngitis. And sensitivity to Amoxicillin and Cephalexin was 41.2% and 13.7%. There was No association between the presence of these superantigens and resistance to Amoxicillin and Cephalexin. There was significant association between the patients having SpeA gene and the presence of cervical lymphadenopathy. There was significant association between the patients having SpeB gene and presence of fever.